STRATEGY FOR MICRO AND SMALL BUSINESSES DEVELOPMENT IN THE FISHERIES SECTOR IN NORTH HALMAHERA REGENCY, INDONESIA - Hendriane Namotemo; Femsy Kour; Anita Dilly; Febrina Akerina; Anggeline Amahorseja (School of Business, IPB University (SB-IPB), 2021)
Micro and small enterprises (MSEs) play a vital role in the sustainability of regional economic development. The fisheries and agriculture sectors are the two leading sectors in North Halmahera Regency, contributing around 23% of the region's Gross Regional Domestic Product (GRDP). The purpose of this study is to identify external and internal factors that influence the development of fisheries MSEs and to formulate a strategy for developing MSEs in the fisheries sector. The data was collected using interviews with 30 respondents and focus group discussions. The analysis used external factor analysis (EFAS), internal factor analysis (IFAS), and SWOT analysis to formulate a strategy for developing MSEs' players. The results of the interviews show fisheries MSEs face challenges such as lack of infrastructure, limited capital, and limited competence in the fishery process. According to the IFAS results, the fisheries MSEs in North Maluku have a more significant weakness score than the strengths indicated by the score -0.49. Based on EFAS results, the fisheries MSEs in North Maluku have more significant opportunities than threats. The SWOT analysis indicates the MSEs in the fisheries sector in North Halmahera are in quadrant II, which supports a potential development strategy, including market development, market penetration, product development, and horizontal integration. Keywords: Micro and small business, fishery, Strategy development, SWOT, EFAS, IFAS